The international copyright protection and the clash between the copyright and droit d'auteur systems (Revista do Tribunal Regional Federal da 3ª Região, 2011)
The text deals with the international protection of copyright and the clash between the copyright and droit d'auteur systems. It shows how the two different systems of author protection have influenced the construction of international rules on the subject.
Keywords: internactional law; copyright; droit d'auteur